2021
DOI: 10.1093/ntr/ntab073
|View full text |Cite
|
Sign up to set email alerts
|

A Multicenter, Double-Blind, Randomized, Placebo-Controlled Phase 2b Trial of Cytisinicline in Adult Smokers (The ORCA-1 Trial)

Abstract: Introduction Cytisinicline (known as cytisine), a nicotinic acetylcholine receptor partial agonist, is a smoking cessation aid currently marketed in Central and Eastern Europe using a 1.5mg/tablet 25-day downward titration schedule. No prior studies have evaluated other doses or administration schedules. This study evaluated effects of a higher dosage and simplified dosing schedule on drug efficacy and tolerability. Methods O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
29
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 17 publications
0
29
0
2
Order By: Relevance
“…Cytisinicline’s mean elimination half-life of 4.8 hours supports a simplified regimen using 3 times daily administration . In a randomized phase 2b trial testing various doses and schedules for 25 days, 3 mg administered 3 times daily produced the highest biochemically confirmed continuous abstinence during 4 consecutive weeks after treatment ended (weeks 4 to 8) and was superior to placebo (30% vs 8%, P = .005) . The 3-mg dose taken 3 times daily was well tolerated, achieved good treatment adherence, and was selected for use in phase 3 clinical trials …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cytisinicline’s mean elimination half-life of 4.8 hours supports a simplified regimen using 3 times daily administration . In a randomized phase 2b trial testing various doses and schedules for 25 days, 3 mg administered 3 times daily produced the highest biochemically confirmed continuous abstinence during 4 consecutive weeks after treatment ended (weeks 4 to 8) and was superior to placebo (30% vs 8%, P = .005) . The 3-mg dose taken 3 times daily was well tolerated, achieved good treatment adherence, and was selected for use in phase 3 clinical trials …”
Section: Introductionmentioning
confidence: 99%
“…9,14 In a randomized phase 2b trial testing various doses and schedules for 25 days, 3 mg administered 3 times daily produced the highest biochemically confirmed continuous abstinence during 4 consecutive weeks after treatment ended (weeks 4 to 8) and was superior to placebo (30% vs 8%, P = .005). 15 The 3-mg dose taken 3 times daily was well tolerated, achieved good treatment adherence, and was selected for use in phase 3 clinical trials. 15 Because relapse commonly occurs early in a quit attempt, a treatment duration longer than 25 days might improve the effectiveness of the revised cytisinicline regimen.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A simplified dosing regimen for cytisine with a more standard extended schedule may lead to enhanced treatment adherence and increased effectiveness but must be balanced against a tolerable adverse event profile. Although the results from a recent placebo-controlled trial and an active comparator trial of cytisine with amended dosing have shown some promise, future studies may provide additional insights about revised treatment dosing of cytisine …”
mentioning
confidence: 99%
“…Cytisine is an effective and well-tolerated smoking cessation aid . A relative lack of private investment has stifled production of and wider access to cytisine .…”
mentioning
confidence: 99%